A tutela dos direitos fundamentais das vítimas de crimes patrimoniais no ordenamento jurídico brasileiro - Karina Ribeiro dos Santos Vedoatto (2023)
The ineffectiveness of the fundamental rights of victims of property crimes in the Brazilian legal system requires a re-reading of the treatment given to those offended by the operators of the criminal justice system. Thus, through a deductive methodology, carried out through bibliographical, documentary and jurisprudential research, it was seen that, with the atrocities resulting from the 2nd World War, which culminated in a macro victimization never experienced before, a movement of recognition began. the fundamental rights of criminal victims; in addition to identifying the phenomenon of victimization, its causes, types and consequences, from which international documents emerged recognizing different rights to the offended, followed by national or domestic norms, both at the constitutional and infraconstitutional levels. However, in spite of the validity of such protective regulations, in the practice of the Brazilian criminal and procedural system, it is commonly seen that there is a disrespect for the human dignity of victims in the face of the lack of effectiveness of their fundamental rights. Thus, in view of the absence of effective and efficient protection of the fundamental rights of victims of property crimes, the research sought, after analyzing the victimological movement, the role of the victim in the penal system throughout history and the phenomenon of victimization, to identify the rights already regulated and those that are still pending regulation, such as the creation of a Public Fund to repair the damage caused by the commission of the crime; as well as the reasons for their non-effectiveness in the Brazilian legal system, ending by analyzing possible mechanisms or ways to ensure, in practice, the effective protection of such rights. And, in the end, the research pointed out some suitable, accessible and effective means and instruments in the realization of the rights and interests of those offended by crimes committed in the national territory, such as: the exercise of control of the conventionality of internal laws in relation to the Treaties of Rights Human rights ratified by Brazil and the jurisprudence of the International Courts, to be exercised ex officio by the competent authorities and bodies, as legitimized by the Inter-American Court; the correct application of the instruments of Consensual Justice foreseen in the internal legal system and, also, of the Theory of Criminal Guarantee, which must be fully applied, in order to cover all the fundamental rights foreseen in the CF; the replication of the good performance practices of some Public Ministries in favor of criminal victims, carried out through Projects and Programs aimed at meeting the needs of the offended and respecting their fundamental rights; the development in the country, in the States and in the Municipalities of victimization surveys, such as a criminal policy that covers primary victimization and enables the development of public policies aimed at preventing the occurrence of crime and welcoming and guiding victims of crime. Thus, demonstrating possible solutions to the current problem of the human or fundamental rights of the offended, guaranteeing and putting them into effect.